Using the health belief model to assess beliefs and behaviors regarding cervical cancer screening among Saudi women: a cross-sectional observational study - Arwa I. Aldohaian; Sulaiman A. Alshammari; Danyah M. Arafah (BMC, 2019)
Abstract Background Cervical cancer in Saudi Arabia is ranked as the third most frequent gynecological cancer among women. The Pap smear test is a screening test that can be used as a primary prevention tool for cervical cancer, and prophylactic vaccination against HPV is also considered to be a factor in decreasing the prevalence of the disease. This study aimed to assess women's beliefs about cervical cancer and the Pap smear test. In addition, the relationship between cervical cancer and the social and demographic characteristics was also evaluated. Methods A descriptive cross-sectional study was performed among Saudi women living in Riyadh in 2018. Women were randomly selected, and the total sample size was 450. A predesigned self-administered questionnaire that included the Health Belief Model scale was used to collect data. Data were analyzed using SPSS 21.0. P values < 0.05 were considered as statistically significant in this study. Results Among the 450 participants, the Pap smear test uptake was 26% and the HPV vaccine uptake was less than 1%. A low education level and family history for cervical cancer were significantly associated with the belief of high susceptibility for developing cervical cancer (p < 0.05). The seriousness of the disease was recognized by 38%, and the benefit of screening was recognized by 82% of the participants. In addition, 27% of the participants perceived barriers to obtaining a Pap smear test. Conclusions This study showed a high level of perception regarding benefits and motivation, and a low incidence of perceived barriers among women regarding cervical cancer screening. However, these attitudinal aspects did not translate into practice, as reflected by the low uptake of the screening test. Our findings imply that concerted efforts are needed to promote cervical cancer screening programs in Saudi Arabia. In view of the planned implementation of Saudi vision 2030, which emphasizes on prevention, we recommend launching a national cervical cancer screening program, to be available and accessible to all women in primary health care centers and hospitals.